UPAYA PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING DENGAN METODE EKSPERIMEN PADA SISWA KELAS IV - Yuliani, Rita; Relmasira, Stefanus C. (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2017)
Abstract: This research is based on the low percentage of achievement on Minimum Exhaustiveness Criteria obtained by fourth grade students of SD Sidorejo Lor 07 from thenumber of students 43 people who follow the Middle Semester's Deuteronomy onmaterial nature of the body. The result of this TOD is learning with CTL (ContextualTeaching and Learning) Model By Experiment. Researchers are motivated to conductClassroom Action Research to improve science learning outcomes in Sidorejo Lorelementary school 07. KKM score set by science subjects in grade IV â‰¤68. Prasikluslearning results show the value of completeness of learning results only reached 27.90%of 43 students. Researchers take action using CTL (Contextual Teaching and Learning)model with Experiments. The target set by researchers for student achievement reaches80%. The first cycle of learning results has increased to 51.16% or 22 students whoselearning outcomes are complete. Then the cycle 2 needs to be done because it has notreached the target that ditntukan. In Cycle 2 the results of learning increased again to81.39% or 35 students have complete learning outcomes. This research proves that theimplementation of CTL (Contextual Teaching and Learning) model with Experiments canimprove science learning outcomes in SD Sidorejo Lor 07 Sidorejo Sub-district SalatigaCity.Keywords:CTL (Contextual Teaching and Learning) Model, Experiments,, Learning Outcomes, Science. Abstrak : Penelitian ini di latarbelakangi oleh rendahnya persentase ketercapaian atasKriteria Ketuntasan Minimal (KKM) yang diperoleh siswa Kelas IV SD Sidorejo Lor 07dari jumlah siswa 43 orang yang mengikuti Ulangan Tengah Semester pada materi sifatwujud benda. Adapun hasil PTK ini adalah pembelajaran dengan Model CTL (ContextualTeaching and Learning) Dengan Eksperimen. Peneliti termotivasi untuk melakukanPenelitian Tindakan Kelas untuk memperbaiki hasil belajar IPA di SD Sidorejo Lor 07.Nilai KKM yang ditetapkan mata pelajaran IPA di kelas IV â‰¤68. Hasil belajar prasiklusmenunjukan nilai ketuntasanhasil belajar hanya mencapai 27,90 % dari 43 siswa. Penelitimelakukan tindakan dengan menggunakan model CTL (Contextual Teaching andLearning) Dengan Eksperimen. Target yang ditetapkan peneliti untuk hasil belajar siswamencapai 80%. Siklus I hasil belajar sudah meningkat mencapai 51,16% atau 22 siswayang hasil belajarnya tuntas. Kemudian perlu dilakukan siklus 2 karena belum mencapattarget yang ditntukan. Pada Siklus 2 hasil belajar meningkat kembali menjadi 81,39%atau 35 siswa telah tuntas hasil belajarnya. Penelitian ini membuktikan bahwaditerapkannnya model CTL (Contextual Teaching and Learning) Dengan Eksperimendapat meningkatkan hasil belajar IPA di SD Sidorejo Lor 07 Kecamatan Sidorejo KotaSalatiga.Kata kunci: Model CTL (Contextual Teaching and Learning), Eksperimen, , Hasil Belajar, IPA.